Silencing of Long Noncoding RNA Growth Arrest–Specific 5 Alleviates Neuronal Cell Apoptosis and Inflammatory Responses Through Sponging microRNA-93 to Repress PTEN Expression in Spinal Cord Injury - Cao, Yuanwu; Jiang, Chang; Lin, Haodong; Chen, Zixian (Frontiers in Cellular Neuroscience, 2021)
A secondary injury induced by a spinal cord injury (SCI) remains the main cause of devastating neural dysfunction; therefore, it has been the subject of focused research for many years. Long noncoding RNA (lncRNA) has been found to participate in the SCI process, and this finding presents a high potential for diagnosis and treatment; however, the role of lncRNA in a secondary injury induced by SCI remains unclear. The aim of this study was to investigate the regulatory effect of lncRNA growth arrest–specific transcript 5 (GAS5) in secondary injury during SCI. The SCI mice model and hypoxic cellular model were established to research the roles of lncRNA GAS5 during SCI. Reverse transcription quantitative polymerase chain reaction (qRT-PCR) was conducted to determine the expression levels of microR-93 (miR-93) and lncRNA GAS5. Western blot analysis of the apoptosis regulator protein and terminal deoxynucleotidyl transferase dUTP nick end labeling assay were conducted to evaluate neuron cell apoptosis. Basso, Beattie and Bresnahan (BBB) scores were calculated to assess neurological function. Flow cytometry was used to determine neuron cell apoptosis. The associations among GAS5, miR-93, and the phosphatase and tensin homolog (PTEN) were disclosed using RNA immunoprecipitation (RIP) assay, RNA pulldown assay, and dual-luciferase reporter assay. QRT-PCR demonstrated that GAS5 was significantly upregulated in both the SCI mice and hypoxic cellular models. GAS5 knockdown suppressed neuron cell apoptosis and inflammatory response in the SCI mice model. Further studies have indicated that GAS5 functions as a competing endogenous RNA (ceRNA) by sponging miR-93 in neuronal cells. In addition, PTEN was a target of miR-93, and GAS5 knockdown exhibited its anti-apoptotic and anti-inflammatory effects through the miR-93/PTEN axis. These findings suggest that the GAS5/miR-93/PTEN axis may be a promising therapeutic target for SCI.